Peran Mahasiswa Hukum dalam Peningkatan Literasi Bahasa Indonesia dan Pembangunan Desa: Studi di Desa Kelilik - Bhagawanta Atyuta Pradhana; Muhammad Afarly Meliala; Sabrina Bernoza Hanifah; Mella Kartika Putri; Wevy Efticha Sari (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2025)
The role of law students in improving literacy and the use of Indonesian in Kelilik Village, as part of a community development strategy based on education and law. The background of this research is based on the low level of literacy and Indonesian language skills which remain a serious challenge in rural areas, thus having implications for limited community access to information, education, and participation in legal and social development. The formulation of the research problem focuses on the contribution of law students in improving the quality of literacy in rural communities and the synergy patterns established with the Ministry of Villages, Development of Disadvantaged Regions, and Transmigration. By using a qualitative approach and descriptive analysis through literature studies, it was found that law students not only function as literacy facilitators and advocates for the use of good and correct Indonesian, but also as liaison actors between village communities and central government policies within the framework of sustainable development. Synergy with the Ministry of Villages shows the existence of program integration that strengthens the sustainability of literacy activities, while supporting the human resource development agenda in the village. This study concludes that law students play a strategic role as agents of change who are able to bridge the literacy gap and foster legal awareness by strengthening Indonesian as an instrument for social, educational, and legal development in rural areas.